CROSS-BORDER MEDICAL TOURISM: A TYPOLOGY AND AGENDA FOR RESEARCH FOR THE SOUTH-EAST ASIAN REGION - KAI-LIT PHUA (Centre For Tourism Planning and Development, 2008)
Cross-border medical tourism can be broadly divided into two types, i.e. price-sensitive and quality sensitive. Price-sensitivity increases the likelihood of